PERAN POLA ASUH DEMOKRATIS ORANG TUA TERHADAP KEMANDIRIAN ANAK USIA DINI - Susanti, Desi; Ismaniar, Ismaniar (Education For All, 2022)
Abstrak The situation that drives writing is a phenomenon that occurs in the family environment from parents who don't really know how to educate the wrong children from an early age. The purpose of this paper is to tell parents the right way of parenting to prepare their children to be independent from a young age. Parents know the role of democratic parenting on the independence of early childhood. The writing uses a literature study. The result of this paper is democratic parenting as the basis for how children have their own initiative in doing things that support independence.